1998
DOI: 10.1007/s007020050127
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid selenium and chromium levels in patients with Parkinson's disease

Abstract: We compared CSF and serum levels of selenium and chromium, measured by atomic absorption spectrophotometry, in 28 patients with Parkinson's disease (PD) and 43 matched controls. The CSF and serum levels of these trace metals did not differ significantly between PD patients and controls. CSF selenium and chromium levels were not correlated with age, age at onset, duration of the disease, scores of the Unified Parkinson Disease Rating Scale of the Hoehn and Yahr staging in the PD group. Although antiparkinsonian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 19 publications
2
22
1
2
Order By: Relevance
“…In the case of patients, the differences among the groups enrolled in the diverse studies are amplified by some clinical variables, as duration and severity of the disease along with medical treatments and possible comorbidities. Regarding duration and severity of the disease, in the trial by Aguilar et al (1998) Se and Cr levels showed no correlation with age at onset and duration of the illness. On the other hand, Alimonti et al (2007b) detected in patients a negative association of Cr amount and severity and duration of the illness; in the same study, Pb appeared to be negatively related to the severity of the disorder, while Sn resulted to be negatively associated with the duration of the disease.…”
Section: Considerations On Factors Influencing the Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…In the case of patients, the differences among the groups enrolled in the diverse studies are amplified by some clinical variables, as duration and severity of the disease along with medical treatments and possible comorbidities. Regarding duration and severity of the disease, in the trial by Aguilar et al (1998) Se and Cr levels showed no correlation with age at onset and duration of the illness. On the other hand, Alimonti et al (2007b) detected in patients a negative association of Cr amount and severity and duration of the illness; in the same study, Pb appeared to be negatively related to the severity of the disorder, while Sn resulted to be negatively associated with the duration of the disease.…”
Section: Considerations On Factors Influencing the Resultsmentioning
confidence: 80%
“…In the reviewed papers, only a few teams give full details of the selection criteria used. The researchers of the Italian Istituto Superiore di Sanità (ISS), Bocca, Forte, Alimonti and coworkers, along with the Spanish scientists (Jiménez-Jiménez et al 1998 andAguilar et al 1998) are among the few authors who describe extensively the criteria employed. The diseases affecting the individuals recruited as patients or controls are often not precisely described, mainly in the less recent works.…”
Section: Considerations On Factors Influencing the Resultsmentioning
confidence: 99%
See 3 more Smart Citations